Menguak Potensi Tersembunyi Kebun Anggur: Analisis Pengelolaan dan SOP Agro Secino dalam Memenuhi Kebutuhan Pasar - Yunita, Yunita; Yunus, Mukhammad Aji Ikhwanul; Mirbah, Kholaf; N, M. Abror Ulin; Sukmawati, Sukmawati (CV.ITTC INDONESIA, 2025)
This research aims to identify the hidden potential of the Yangkung Agro Secino Vineyard in Semarang, which was founded in 2018. In the era of globalization and changing consumption patterns, there is an increasingly urgent need to diversify agricultural products, including the development of grape varieties that were previously little known in Indonesia. This research describes the challenges faced in cultivating grapes in tropical climates, such as adaptation to temperature, rainfall, and pest and disease attacks. This garden also adopts environmentally friendly cultivation methods using organic pesticides and innovative farming techniques. In addition, Yangkung Agro Secino has an edu-tourism program which aims to educate the public about modern agriculture and sustainability. The main challenges faced include high investment costs and uncertainty of harvest results, as well as competition in marketing local products with imported grapes. Through SWOT analysis, this research identifies the strengths, weaknesses, opportunities and threats that influence the success of this garden. It is hoped that with national certification and collaboration with local communities, this vineyard can contribute to agricultural innovation in Indonesia and strengthen the position of local products in the market.